2019
DOI: 10.5650/jos.ess19098
|View full text |Cite
|
Sign up to set email alerts
|

Palm-Pressed Mesocarp Fibre Oil as an Alternative Carrier Oil in Emulsion

Abstract: Introduction Palm oil milling process includes seven main processes which are fresh fruit bunches reception, sterilization, threshing, digestion, mashing and pressing, crude oil clarification and palm kernel recovery which have resulted in tremendous by-products. The available by-products, in various forms or types, are palm oil mill effluent, empty fruit bunches, palm oil mill sludge, decanter cake, palm kernel shells and palm-pressed mesocarp fibres 1. A number of approaches to process the substantial amount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Palm pressed fiber is a form of recovered fiber from pressed palm fruits which is rich in carotenoids, vitamin E (tocopherol and tocotrienols), and sterols, and has been used for the recovery of palm pressed fiber oil which contains significant quantities of carotenoids (4000-6000 ppm), vitamin E (2400 3500 ppm), sterols (4500-8500 ppm), and coenzyme Q10 quantities greater than those found in crude palm oil [131]. As a result, palm pressed fiber oil has antioxidant and anti-inflammatory properties [132] which can be applied in the development of functional foods. The presence of phosphorus in palm pressed fiber oil further enhances its antioxidant properties, and this phosphorus can be extracted for use as a food additive [133].…”
Section: Products From Palm Pressed Fibrementioning
confidence: 99%
“…Palm pressed fiber is a form of recovered fiber from pressed palm fruits which is rich in carotenoids, vitamin E (tocopherol and tocotrienols), and sterols, and has been used for the recovery of palm pressed fiber oil which contains significant quantities of carotenoids (4000-6000 ppm), vitamin E (2400 3500 ppm), sterols (4500-8500 ppm), and coenzyme Q10 quantities greater than those found in crude palm oil [131]. As a result, palm pressed fiber oil has antioxidant and anti-inflammatory properties [132] which can be applied in the development of functional foods. The presence of phosphorus in palm pressed fiber oil further enhances its antioxidant properties, and this phosphorus can be extracted for use as a food additive [133].…”
Section: Products From Palm Pressed Fibrementioning
confidence: 99%
“…Palm‐pressed mesocarp fiber is mainly used as the burning fuel in the boilers [48] and to generate electricity in the palm oil mills. The piling up of PPMF under high humidity conditions may cause environmental issues such as microorganism incubation and release of methane gas and odour.…”
Section: Palm‐pressed Mesocarp Oil and Crude Palm Oilmentioning
confidence: 99%
“…On the contrary, it has been found to contains various types of phytonutrients, including vitamin E, carotenoids, tocopherol, tocotrienols, squalene, phytosterol and coenzyme Q10 4−6) . However, its applications are limited to non-food industry such as cosmeceutical products, supplementary ingredients for animal feed formulation and alternative carrier oil in personal care products 5,7) . The commercial oils such as perilla (Perilla frutescens) seed oil 8) , fermented virgin pathological indicators, organ weight and histopathological indicators of the animals 8,9) .This study reported the thresholds of PPMO in terms of animal exposure and safety by conducting the acute and sub-chronic toxicity studies of PPMO in Sprague-Dawley rats.…”
Section: Introductionmentioning
confidence: 99%